(untitled) (Palíndromo, 2016)
There is a reflection on the acade- mic research whether dissertation or the- sis through the texts “Escrever” by Mar- guerite Duras, “A revisão da bibliografia em teses e dissertações: meus tipos ines- quecíveis – o retorno” and “Viver a tese é preciso.” The last two were taken from the book “A bússola do escrever”, and it is possible to relate the texts with the thesis “A representação da cidade de Flo- rianópolis na visão dos artistas plásticos” by the Dr. Professor Sandra Makowiecky. It is carried out an analysis of the disser- tation project by reading images, histori- cal context, artist luggage, and memory. The article’s aim is to understand the im- portance of conducting a research and analyzing it as a multiplier element of knowledge.